2021
DOI: 10.1002/htj.22365
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Dufour and Soret effects on the non‐Darcy flow of Cross fluid by a tilted plate with radiation and chemical reaction: A Cattaneo–Christov heat flux model

Abstract: The Darcy-Forchheimer flow model is substantial in the fields where a high flow rate effect is a common phenomenon, for instance, in petroleum engineering. In this paper, we aim to scrutinize the aspects of crossdiffusion effects on the non-Darcy flow of Cross fluid by a tilted plate with thermal radiation and chemical reaction. Metamorphosed equations are resolved with the combination of shooting and Runge-Kutta fourth-order procedures. The correlation coefficient is used to discuss the impact of pertinent pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The Cross-fluid is optically thick, hence the Rosseland approximation for thermal radiation is adequate to model. Thus, according to the linearized Rosseland approximation, the thermal radiative heat flux (𝑞 𝑟 ) is given below (see references [8,33]):…”
Section: Flow and Heat Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…The Cross-fluid is optically thick, hence the Rosseland approximation for thermal radiation is adequate to model. Thus, according to the linearized Rosseland approximation, the thermal radiative heat flux (𝑞 𝑟 ) is given below (see references [8,33]):…”
Section: Flow and Heat Transfermentioning
confidence: 99%
“…The consequence of the Winsberg number on the dynamics of Cross-fluids at the point of stagnation was analyzed by Hayat et al [27] and found a negative impact on the movement of the Cross fluid. In this direction, many investigators (Shahzad et al [28], Kim [29], Hosseinzadeh et al [30], Al-Kouz et al [31], Ayub et al [32], Rao et al [33], and references therein) were studied dynamics of Cross fluid over different geometries subject to different physical effects. However, the study of flow and heat transfer of Cross fluid in an inclined micro channel subjected to non-linear density variation and Newton boundary condition has not been considered yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the incorporation of nanoparticles, thermal conductivity is increased and hence rapid heat transport takes place. Nanofluid has vital applications in engineering, 1–5 chemical industry, 6–10 and in thermal science, 11–14 and so forth. Mahian et al.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the incorporation of nanoparticles, thermal conductivity is increased and hence rapid heat transport takes place. Nanofluid has vital applications in engineering, [1][2][3][4][5] chemical industry, [6][7][8][9][10] and in thermal science, [11][12][13][14] and so forth. Mahian et al's 15 valuable work related to fundamentals and theory about advancement in modeling of nanofluid flows.…”
Section: Introductionmentioning
confidence: 99%